If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8b-6=-7b
We move all terms to the left:
-8b-6-(-7b)=0
We get rid of parentheses
-8b+7b-6=0
We add all the numbers together, and all the variables
-1b-6=0
We move all terms containing b to the left, all other terms to the right
-b=6
b=6/-1
b=-6
| 2x+56=92 | | 10y-6=8y+33 | | 9u=-45 | | 8-(6x+5)=9 | | 180+0.25x=350 | | 2x/10=16(1/2) | | -16t^2+12t+1900=0 | | 108+0.25x=350 | | x^2–6x–16=0 | | x2-14x+20=7 | | 6-(x+8)=3x+6 | | 8x-6x+7)=-1 | | -10+1+y=9-y | | p+-91=-9 | | -4+w=48 | | 2g-5=1 | | 2x+56=88 | | -6+4v=3v | | 9(2a+1)=10(a+5) | | 44x+6=5.5x | | 3v=93 | | 3x+2=−10 | | 20x-7=19x-8 | | 1+10d=6+9d | | 5xN+9=4N+12 | | -7+4k=-19 | | 2x+54=94 | | 5(y/5-3)=30 | | 39x+2)=6(2x+1) | | c-13=-7 | | 6-3y=-4y | | 5(y5–3)=30 |